Effects of low voltage electrical stimulation during bleeding on characteristics of beef loin eye top round muscles - Kropf, Donald H.; Hunt, Melvin C.; Unruh, John A.; Kastner, Curtis L.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Low voltage electrical stimulation (ES) during bleeding and subsequent carcass chilling at 36 to 46° F resulted in 1) a more rapid pH decline 2) initial lighter red color, but more rapid discoloration during display 3) softer and coarser textured lean 4) reduced water holding capacity and juiciness and 5) decreased tenderness of the loin eye longissimus (LE) muscle when compared to the non-stimulated control (C) LE muscle. ES effects on top round semimembranosus (TR) muscle were limited to a more rapid pH decline and lower water holding capacity. Our results indicate that ES soon after slaughter, coupled with relatively slow initial chilling may reduce meat quality. More rapid initial chilling of C and ES carcasses and/or delaying the ES application may be necessary for ES to express its frequently observed desirable results.
Keywords: Beef; Electrical stimulation; Loin eye; Top Round